Topology structure and routing policy based on multilayered clusters in Beidou satellite navigation system - Fei-long LI; Guang-xia LI; Zhi-qiang LI; Feng-bin PENG (Tongxin xuebao)
A dynamic network topology evolution model was established based on multilayered clusters.Moreover,the routing policy was studied from the two aspects of MEO working independently and GEO/MEO working collaboratively.The three-level information transmission and distribution mechanism was proposed via employing cluster manager,cluster head and cluster member.Finally,through the cluster division and boundary nodes selection among the sub-clusters,the scheme achieves the inter-cluster topology change shielded from each other,independent networking routing and sub-cluster information exchange,as well as a low network management complexity and routing calculations.